Effective frame transmitting mechanism for improving the network throughput - WU Da-peng; WU Mu-qing; ZHEN Yan (Tongxin xuebao)
The limited radio resource can be used reasonably by the frame transmitting mechanism well designed.Based on the analysis on the normalize throughput of IEEE 802.11 wireless LAN,combining adaptive contention window and random varying timing method,a simple and effect frame transmitting mechanism was proposed.Actively,the dynamical varying timing method adjusts the number of packets sending to queue;moreover,the adaptive contention window scheme determines the size of contention window based on the collision status rapidly.The simulations show that the mechanism is able to optimize the parameters of packets sending out,and network throughput can be improved 30 per-cent,consequently,the radio resource is utilized more reasonably.